Professional Associations and Agricultural Cooperatives from Romania and U.E. – Key Factor in the Development of Agriculture - Remus Gherman; Tiberiu Iancu; Ana-Mariana Dincu; Ioan Brad (Scientific Papers Animal Science and Biotechnologies, 2023)
Establishment of producers in associative forms open more opportunities for economic development by attracting local, regional advantages, using collective power in order to increase the prosperity of members and communities from which they belong. Worldwide, in last years, farmers are forced to adopt fundamental decisions, namely: activation in unsafe conditions in order to achieve viable agricultural holdings, resistant to competition. The association, with the purpose of a better representation in front of the authorities, is practiced also in Romanian agriculture starting from the 1990. There are in Romania numerous forms of association, both by activities and by specific branches, at county, regional and national level. Associations and national federations have a relevant representation in the territory, these becoming the dialogue partners of the authorities. Organization in professional associations and cooperatives led to improvement of the incomes of its members, strengthening the economic position and providing a service that is needed leading, ultimately, to the progress of agriculture in general. In U.E. countries, agricultural cooperatives are founded in shapes and types that vary by countries, but witch in essence have the same principles of organization and functioning. Agriculture of U.E. associates in cooperatives, called of first degree, which have as purpose realizing of the investments in upstream and downstream of agriculture for collection or processing of agricultural products. Third degree cooperatives are organized by participating of cooperatives of second degree, forming powerful financial, commercial and industrial groups. Professional associations and agricultural cooperatives from European Union, formed and consolidated over decades, plays a key role in obtaining performant products and high profits for farmers from those countries.